Attenuation of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) neurotoxicity by the novel selective dopamine D3-receptor partial agonist FAUC 329 predominantly in the nucleus accumbens of mice - Gmeiner, Peter; et al. (Biochemical Pharmacology, 2003)
We previously synthesised a novel dopamine (DA) partial agonist FAUC 329 with high affinity and selectivity for the DA D3 receptor. This is the first in vivo study to investigate the protective effects of FAUC 329 in a MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) mouse model of Parkinson's disease. Adult male C57bl/6 mice were injected with FAUC 329 (0, 0.1, 0.5, 0.75, or 1mg/kg) 30min before MPTP (2×30mg/kg, 4hr apart). One week later, accumbal and striatal tissue was processed for DA and metabolite HPLC determination as well as immunohistochemical analysis of DA transporter positive neurons in the substantia nigra pars compacta and ventral tegmental area was carried out. FAUC 329 showed a significant attenuation of MPTP-induced DA reduction in the nucleus accumbens (0.5, 0.75 and 1mg/kg) in a dose-dependent manner. FAUC 329 (0.75mg/kg) partly protected against DA depletion in the dorsal striatum as well as protected against loss of DA transporter immunoreactivity in the substantia nigra pars compacta. The highest dose of FAUC 329 (1mg/kg), however, showed a non-significant tendency to augment the MPTP-induced striatal DA reduction. The protective effect of FAUC 329 against MPTP-induced DA depletion was most pronounced in the nucleus accumbens and appears to be linked to the preferential abundance of D 3 receptors in this region. Targeting the mesolimbic DA system may have implications for improvement of impaired motor behaviour and particularly non-motor functions related to the nucleus accumbens. © 2003 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.lphch.attenu
Keywords: Dopamine D; FAUC 329; MPTP; Neuroprotection; Nucleus accumbens; Parkinson's disease